OPTIMIZING SURGICAL OUTCOMES IN LAPAROSCOPIC SLEEVE GASTRECTOMY THE ROLE OF STAPLE LINE OVERSEWING IN ENHANCING PATIENT SAFETY AND EFFICACY - Dr. Faheem Khan; Waleed Anjum; Aqsa Amin; Mohammad Yassin (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Purpose: This paper aims to compare staple line oversewing concerning postoperative complications, patient satisfaction and cost-effectiveness in a laparoscopic sleeve gastrectomy (LSG) setting. Since there is still controversy about the utilization and efficiency of staple line reinforcement, the present paper attempts to present data that would complement common knowledge.Objective: The primary objectives are to determine whether staple line oversewing reduces the incidence of postoperative leaks and bleeding, enhances better management of patient pain and satisfaction rates and identifies cost-effectiveness in Laparoscopic sleeve gastrectomy (LSG) procedures.Methodology: In the current study, quantitative, cross-sectional research was used, and the study recruited 210 Laparoscopic sleeve gastrectomy (LSG) patients. Thrown for structured questionnaires and medical records were also analyzed, if any. To evaluate the effect of staple line oversewing, various descriptive statistical tests such as Independent Samples T-Tests, Mann-Whitney U Tests, Pearson Correlation and inferential statistical test Logistic Regression were used. Furthermore, the study also engaged in data visualizations with the application of bar plots, box plots, scatter plots, and coefficient plots for purposes of comparing the results of the interventions between groups and testing the strength in association with the variables. The evaluation of cost-effectiveness was done utilizing the cost-benefit analysis considering such costs that might be directly and indirectly linked with the procedure.Results: By analyzing the experimental results, the researchers have found out that there was no statistically significant difference between the two groups; the oversewing group and the no oversewing group, so the result was calculated with the p-value of 0.284. Likewise, the rate of bleeding was also in a similar percentage (p=0.337). The level of pain management did not reach statistically significant whether oversewn or not (mean difference 0.2 p 0.412); similarly, the overall patient satisfaction was similar (median difference 0.3 p= 0.465). Thus, Pearson correlation analysis showed that age was not related to pain management scores r = -0.05 p = 0.721. The Statistical test applied logistic regression and revealed that age has a significant relationship with Postoperative Complication (Odds Ratio= 1.75, p=0.041); however, BMI category and oversewing were not found to have any significant relationship. The cost advantage study showed that the added cost of oversewing as compared to the standard suture was not compensated by reduced costs due to complications, thereby reporting very slight economic merits of oversewn sutures (p= 0.589). The bar graph and Box graph further ensured that differences in the results of processes involving oversewing and non-overswinging were also statistically insignificant.Practical Implications: This indicates that perhaps staple line oversewing is not needed in every Laparoscopic sleeve gastrectomy (LSG) as there was no substantial decrease in the complications and proved to be financially unwise. It can be suggested that, based on these results, surgeons should base their decisions related to oversewing on several risk factors of a specific patient and use the method mostly where the possibilities of complications are higher. Novelty: Taking a closer look at Laparoscopic sleeve gastrectomy (LSG), this work discusses the necessity of utilizing staple line oversewing, as well as its effectiveness and influence on patients’ outcomes and the healthcare cost and raises a question about the rationale of such an untamed practice in Laparoscopic sleeve gastrectomy (LSG).Conclusion: Oversew of the staple line in laparoscopic sleeve gastrectomy is not of great value because it does not decrease postoperative complications, there is almost no difference in patient-reported outcomes and does not save many costs. Such studies indicate that targeted application of this technology based on the patient’s characteristics may be more suitable than conventional approaches. Future work is still required to provide more effective guidelines and develop best Surgical practices in Laparoscopic sleeve gastrectomy (LSG).